Personal nationalism in Slavic immigrant communities in Argentina during the Cold War (1955-1960) - Galvan, Valeria (Revista de Historia Social y de las Mentalidades, 2025)
The objective of this work is to analyse the effects on Argentine soil of the Soviet Repatriation Campaign carried out between 1955-1960. Particularly, the focus is on the Slavic immigrant communities in Argentina and on the subjective consequences in this population of Soviet propaganda in favour of repatriation. In this sense, we analyse biographical accounts of individuals who were convinced to leave Argentine citizenship to repatriate to the USSR but who later repented and tried to appeal to the Argentine state to repatriate them. The originality of this research lies in the intimate perspective, focussed on the way of feeling and appropriating the Nation. The analysis shows that, even when they considered themselves Argentines, these individuals bowed, at first, to the process of Soviet nationalisation "from above" and then reconstructed the narrative that linked them to the Argentine nation. The case of returnees in Argentina thus opens the possibility of studying the way in which personal nationalism acts. The conclusions of this analysis show that the Repatriation Campaign managed to highlight the elements that associated these individuals with the Argentine Nation.
Keywords: displacement of persons; Cold War; personal nationalism